Critical Review of Two-dimensional Slope Stability Analysis by Discontinuity Layout Optimization, Limit Equilibrium and Strength Reduction Methods - Cheng Y M.. (Global Journals of Research in Engineering, 2023)
While the limit equilibrium and finite element methods have been used by the engineers for a variety of slope stability problems for many years the use of limit analysis has started to attract the attentions of engineers and researchers in recent years In this paper the differences between these three major methods will be studied in terms of factors of safety and the locations of critical failure surfaces